Step-by-step explanation:
so, I understand, we have
(3m³)³
well, it is not very long, but the "exponent of an exponent" can be combined.
so, this expression is
3³m⁹ = 27m⁹
and that is the shortest form.
remember, if we multiply the same base multiple times with various exponents, we simply add the exponents.
like m³×m² = m⁵
if we we put a term with exponent again to the power of something, we multiply the exponents.
like (m³)² = m⁶
or (m⁵)⁴ = m²⁰
because
(m⁵)⁴ = m⁵×m⁵×m⁵×m⁵
and as before, we would now add the exponents.
5+5+5+5 = 20
and this is also, as we know from basic calculations
5×4 = 20
and also remember, when putting a term to the power of something, and that term consists of several factors (like 3 and m for 3m), then we need to apply that exponent to all factors.